Physical and chemical investigation of water and sediment of the Keban Dam Lake, Turkey: Part 2: Distribution of radioactivity, heavy metals and major elements - Kulahci, F.; Do?ru, M. (My University, 2006)
Thirtynine surface water and 20 deep sediment samples were taken in different locations in Keban Dam Lake (Elazig, Turkey) to identify major sources and assess major elements, heavy metals, 137Cs, 90Sr, total alpha- and, total beta-distribution in 2003 and 2004 in four seasons each year. As a preliminary study heavy metal (Zn, Fe, Mn, Ni, Cu, Cr, and Co), major element (Mg, Ca, Na, K) and radioactivity concentrations of 137Cs, 90Sr, total-? and total-? in the surface water and deep sediments were determined. © 2006 Akadémiai Kiadó.
Keywords: calcium; cesium 137; chromium; cobalt; copper; heavy metal; iron; lake water; magnesium; manganese; nickel; potassium; sodium; strontium 90; surface water; zinc; article; concentration (parameters); environmental radioactivity; radiation measurement; radioactive pollution; seasonal variation; sediment; Turkey (republic); water analysis; water pollution